Autonomous Robots and Their Legal Regime in the Context of Recodification of Civil Legislation of Ukraine - Khodyko, Yurii (Law, State and Telecommunications Review, 2023)
[Purpose] The issues of understanding what a robot is as an object of civil legal relations and the civil law regime that must be applied to ensure effective legal regulation of relations related to the use of robotics require legal solutions. Special attention should be paid to the study of liability for damage caused by robotics to a person or their property. [Methodology/Approach/Design] The main methods on which this work was based are the method of systematization and the method of analysis. The article summed up various basic materials related to robots as objects of civil legal relations, as well as the impact of their existence on the current development of the world. [Findings] Considering the purpose of robotics in the modern world, it is proposed to carry out legal regulation of robotics relations using an approach of the extension of civil law regulation applied to things. This does not exclude the introduction of special rules that will apply exclusively to robots as objects.